2000
DOI: 10.1179/026708400101517008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of multilayer pvd Ti/TiB2 coatings

Abstract: To obtain from a tribological perspective acceptable PVD coatings of covalently bonded materials, such as borides and oxides, it is essential to control and often reduce the very high compressive stresses which develop during coating growth, since such stresses not only reduce coating adhesion but also limit film thickness. A possible way to obtain lower stress levels could be to utilise multilayer coatings, that is to combine the stressed material with a more ductile material in a layered structure. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…• C of amorphous overstoichiometric TiB x coatings (of B/Ti ratio value in the range 2-2.45), formed by MS at room temperature condition, resulted in crystallization of equilibrium hexagonal TiB 2 phase as columnar grains of 5-10 nm in diameter, oriented along [001] direction [7,8], while excess boron formed thin layer (a tissue layer) separating TiB 2 grains. It was shown that this orientation was unchanged during annealing of the coating up to 800…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C of amorphous overstoichiometric TiB x coatings (of B/Ti ratio value in the range 2-2.45), formed by MS at room temperature condition, resulted in crystallization of equilibrium hexagonal TiB 2 phase as columnar grains of 5-10 nm in diameter, oriented along [001] direction [7,8], while excess boron formed thin layer (a tissue layer) separating TiB 2 grains. It was shown that this orientation was unchanged during annealing of the coating up to 800…”
Section: Resultsmentioning
confidence: 99%
“…Nanostructured coatings containing amorphous TiB 2 (a-TiB 2 ) were produced by plasmaenhanced CVD in Ti-B-N system [5]. However, coatings containing nanocrystalline TiB 2 phase were produced by PVD methods using bombardment of high-energy ions [7], a negative bias voltage applied to substrates [8] or by crystallization from amorphous phase. Depending on chemical composition of TiB x coating, deposition method, heat-treatment parameters, different temperatures of crystallization of TiB 2 phase are reported: in the * corresponding author; e-mail: atwardow@up.krakow.pl range 900-1100…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent research results on the possibility of improving of surface properties of wear -resistant materials suggest that deposition of coatings by several processes could be a potential solution. 10 However, large compressive stresses can cause failure of the coating by debonding, especially at coating edges. 9 An important factor is that high residual stresses are introduced during postdeposition cooling, which in turn affect the behavior of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…Similar techniques have been used to enhance the adhesion of TiB 2 coating onto steel substrates. 7,8) However, Berger and Larson 9) addressed that the yield strength and fracture strength of titanium interlayers were insufficient to accommodate the level of stresses generated in TiB 2 coatings during deposition and during application. In the present attempt to further improve the adhesion strength of sputtered TiB 2 coatings onto high speed steel (HSS) substrates, chromium was used as the interlayer material.…”
Section: Introductionmentioning
confidence: 99%